IMPLEMENTATION OF NUTRITION WEEK PROGRAM TO MEET CHILDREN'S NUTRITION NEEDS IN PILOT LABORATORY KINDERGARTEN UPI TASIKMALAYA - Nida Diana Hanifa; Nur, Luthfi; Purwati (PG PAUD Universitas Negeri Surabaya, 2025)
Lack of understanding of parents in the importance of balanced nutrition and its impact on children's growth and development is a problem that has emerged and been found today. This study aims to provide access for parents to be involved in programs provided by schools. The method in this study uses descriptive qualitative analysis research. With this method, in-depth analysis is possible to explore information through observation, interviews, and documentation. The analysis shows that the Nutrition Week Program which is carried out routinely every Wednesday is designed with thorough preparation and involves parents in providing food to strengthen the relationship between schools and parents and become a means of education for parents about the importance of balanced nutrition for early childhood. The collaboration between teachers and parents in implementing the Nutrition Week Program to meet children's nutritional needs is a positive synergy to meet the balanced nutritional needs of early childhood. With the Nutrition Week Program, in addition to having an impact on parents, it also helps children grow and develop optimally according to their age and have a good quality of life as provisions in the future. This study is the basis for further research related to the effectiveness of the same program in the long term. In addition, this study is expected to provide an overview of how to implement collaboration between teachers and parents in meeting children's nutritional intake for optimal growth and development.